The Importance of Educational Evaluation in the Teaching and Learning Process at Madrasah Aliyah Ishlahiyah Binjai - Arbeni, Wawan (Holistic Science, 2024)
Learning evaluation has an important role in providing professional decisions, and is a competency that an educator must have. The success of the learning process really depends on the role of a teacher. The interaction between teachers and students is a determining factor in the success of learning, and this process will be effective if it is able to actively involve all students. The importance of evaluation in the learning process lies in its function as a source of valid data about students' abilities. This data will be the basis for teachers in making decisions regarding learning. Apart from that, evaluation also helps educators to improve their quality and classroom management. Therefore, evaluation must be carried out appropriately and thoroughly during the teaching and learning process. Evaluation is not only carried out at the end of the lesson, but should be carried out throughout the learning process. By carrying out appropriate and comprehensive evaluations, educators can obtain accurate information about students' abilities, so they can make the right decisions in learning. Increasing understanding and implementing a good evaluation process will contribute to improving the quality of learning at Madrasah Aliyah Islahiyah Binjai.